An Efficient Trap Passivator for Perovskite Solar Cells: Poly(propylene glycol) bis(2-aminopropyl ether) - Ningli Chen (Nano-Micro Letters, 2020)
Abstract Perovskite solar cells (PSCs) are regarded as promising candidates for future renewable energy production. High-density defects in the perovskite films, however, lead to unsatisfactory device performances. Here, poly(propylene glycol) bis(2-aminopropyl ether) (PEA) additive is utilized to passivate the trap states in perovskite. The PEA molecules chemically interact with lead ions in perovskite, considerably passivate surface and bulk defects, which is in favor of charge transfer and extraction. Furthermore, the PEA additive can efficiently block moisture and oxygen to prolong the device lifetime. As a result, PEA-treated MAPbI3 (MA: CH3NH3) solar cells show increased power conversion efficiency (PCE) (from 17.18 to 18.87%) and good long-term stability. When PEA is introduced to (FAPbI3)1-x(MAPbBr3)x (FA: HC(NH2)2) solar cells, the PCE is enhanced from 19.66 to 21.60%. For both perovskites, their severe device hysteresis is efficiently relieved by PEA.